Time Course of Changes in Extravascular Lung Water Index, Intracranial and Cerebral Perfusion Pressures in Acute Cerebral Circulatory Disorders - Yu. A. Churlyaev; K. V. Lukashev; A. Z. Valiakhmedov; P. G, Sitnikov (Общая реаниматология)
Objective: to study the time course of changes in extravascular lung water index (ELWI) and intracranial and cerebral perfusion pressures (ICP and CPP) and to determine their possible relationships in acute cerebral circulatory disorders (ACCD). Subject and methods. ELWI, pulmonary vascular permeability index (PVPI), ICP, CPP, and central hemodynamics were studied by transpulmonary thermodilution and current X-ray studies were conducted in 18 patients on days 1, 3, 5, and 7 of ACCD. Results. Examinations revealed a supratentorial dislocation of the brain in 6 persons; its subtento-rial dislocation was found in 1 case; supra- and subtentorial dislocations were seen in 6. In patients, ELWI and PVPI increased from days 1 and 5, respectively. The high baseline ICP increased over time. CPP remained unchanged. Preserved left ventricular contractility, enhanced myocardial one, a significant direct correlation between ELWI and PVPI, as well as their increase confirmed that the noncardiogenic genesis was responsible for increased ELWI. A direct significant correlation was found between ICP and ELWI, ICP and PVPI. Against this background, acute respiratory distress syndrome developed in 14 patients with pneumonia evolving in its presence in 7 patients. Conclusion. In ACCD, ELWI increases in the first 24 hours of the acute period. One of its causes is, along with others, primary and/or secondary damage to the brainstem structures with elevated ICP and progressive brain dislocation. The determination of ICP, unlike CPP, is crucial in the diagnosis and treatment of primary/secondary brain injuries and in prognosis. Key words: acute cerebral circulatory disorder, extravascular lung fluid, pulmonary vascular permeability, intracranial pressure, cerebral perfusion pressure, acute respiratory distress syndrome.